Biofilm pigments in temporary streams indicate duration and severity of drying - Miriam Colls; Xisca Timoner; Carme Font; Vicenç Acuña; Sergi Sabater (Limnology and Oceanography, 2021)
Increased duration and frequency of droughts under global change may affect both temporary and formerly permanent watercourses. Streambed desiccation, cooccurring solar radiation, and high temperature all may affect the composition and metabolism of photoautotrophic organisms in benthic biofilms. To test these effects, we characterized the composition of pigments when biofilms were exposed to dry conditions, and compared this to pigments measured after flow resumed, as well as to others measured from permanent streams in the same region. This comparison revealed important differences in pigmentary composition based on flow conditions. Active chlorophylls decreased exponentially with the duration and severity of the nonflow period, while chlorophyll degradation products and protective carotenoids increased. Streams experiencing longer and more severe nonflow periods showed the highest dissimilarities in their biofilm pigmentary composition, and this pattern was maintained after flow resumed. Our results pointed to duration of nonflowing periods as the major driver of pigmentary composition, regardless of whether these were interrupted or not by short intervals of water flows. Multivariate changes in pigmentary composition between sampling periods highlighted the influence of the long‐term hydrological history on the relative abundance of different taxonomic groups and their associated pigments. Overall, pigmentary fingerprints are informative of the biofilm capacity to resist water flow interruption and of their ability to recover after water flow returns.

Effects of Duration, Frequency, and Severity of the Non-flow Period on Stream Biofilm Metabolism - Miriam Colls; Xisca Timoner; Carme Font; Sergi Sabater; Vicenç Acuña (Ecosystems, 2019)

The dynamics of biofilm bacterial communities is driven by flow wax and wane in a temporary stream - Xisca Timoner; Carles M. Borrego; Vicenç Acuña; Sergi Sabater (Limnology and Oceanography, 2014)
Biofilm communities are exposed to long periods of desiccation in temporary streams. We investigated how water flow intermittency affected the bacterial community structure colonizing three different streambed compartments in a Mediterranean stream. Massive parallel sequencing revealed different bacterial communities in biofilms from sand sediments and cobbles. Bacterial communities were similar (62% of shared operational taxonomic units) in the epipsammic and hyporheic biofilms, and more diverse than those in the epilithic biofilms. The non‐flow phase caused a decrease of bacterial diversity in the biofilms, when communities included only bacterial taxa assumed to be adapted to water stress. The most sensitive bacterial communities to flow intermittency were in the epilithic, where the exposure to physical stress was the highest. In sand sediments a wide group of bacterial taxa was tolerant to desiccation. During non‐flow the proliferation of opportunistic taxa in the superficial compartments evidenced the biological link with the terrestrial environment. Bacterial communities better tolerate rewetting than desiccation, since a major number of taxa tolerant to rewetting occurred in all biofilms. Overall, bacterial communities in sandy compartments showed higher resistance to flow intermittency than those in epilithic biofilms.

Photosynthetic pigment changes and adaptations in biofilms in response to flow intermittency - Xisca Timoner; Teresa Buchaca; Vicenç Acuña; Sergi Sabater (Aquatic Sciences, 2014)

Biofilm functional responses to the rehydration of a dry intermittent stream - Xisca Timoner; V. Acuña; L. Frampton; P. Pollard; S. Sabater; S. E. Bunn (Hydrobiologia, 2014)

Microbial biofilm structure and organic matter use in mediterranean streams - Anna M. Romaní; Stefano Amalfitano; Joan Artigas; Stefano Fazi; Sergi Sabater; Xisca Timoner; Irene Ylla; Annamaria Zoppini (Hydrobiologia, 2013)